A poética do olhar: a imagem do trabalhador rural na pintura de Candido Portinari e na fotografia de Sebastião Salgado no processo ensino-aprendizagem - Paulo, Silvia Rosa Marques (2008)
This work was based in a research about a methodology of teaching in Visual Arts applied in high school, in the Public State School Professora Zipporah Rubinstein, located in the Eastern Region of São Paulo city. It aims to used the methodology called Triangular , set out by Anna Mae Barbosa, intending to develop the skills for the appreciation, contextualization and elaboration of poetic proposals of high school students. The research was justified in using images in the classroom and, consequently, there was a preparation to analyze and understand them before making an artistic production. The images are of rural workers and were chosen because it is an issue rarely studied in the field of Arts and little known by students. The proposal was that they meet the artists and their works, the socio-cultural context and history of the time, discussing their life and experiences expressed by the artists, thus creating a new perspective on the current critical condition and really enjoy the importance of the Arts. The methodology used was the qualitative research, which is theoretically based on the Research-Action. In this, the students produced responses in poetic art, by reading, analyzing and contextualizing painting of Candido Portinari and pictures of Sebastião Salgado, reinterpreting and creating new readings of works. The discussions held in this research are related to works that have social meaning, those dealing with the analysis of workers at two specific moments by artists who have different techniques to address the issue. In one part, Portinari paints the frescoes with the theme of workers, on the other, Salgado, using photo focuses on the dimension of those employees who interact with Brazil social.